The reshaping of ancient Israelite history in Chronicles - Kalimi, Isaac (Eisenbrauns, 2005)
This book was awarded the 2006 R. B. Y. Scott award, which is awarded annually by the Canadian Society of Biblical Studies in recognition of an outstanding book in the areas of Hebrew Bible and/or the Ancient Near East written by a member of the CSBS. Kalimi catalogues and categorizes the techniques by which the Israelite history in Samuel--Kings is reshaped in the biblical books of Chronicles. The chapters of this study consider the various historiographical and literary changes found in the parallel texts of Chronicles. Because about half of the material in Chronicles is available to us in other biblical sources, comparison of the literary and linguistic devices used by the Chronicler is very revealing. Kalimi considers the ways in which the Chronicler has edited the material available to him, addressing such topics as: literary-chronological proximity, historiographical revision, completions and additions, various kinds of parallelism and literary devices, and so on. A handy compendium of the ways in which the Chronicler treated his material by one of the premier scholars working in the field.